2021
DOI: 10.1002/ajp.23312
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and anthropogenic effects on the nesting patterns of Nigeria–Cameroon chimpanzees in North‐West Cameroon

Abstract: Environmental conditions and human activity influence the selection of nest sites by chimpanzees and may have serious conservation implications. We examined the characteristics of nesting trees preferred by chimpanzees, investigated the effect of vegetation composition and topography on nest site locations and seasonality on nesting heights of chimpanzees, and verified the effect of predator occurrence and human activity on the nesting behavior of the Nigeria–Cameroon chimpanzee (Pan troglodytes ellioti) in Ko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 71 publications
2
15
0
Order By: Relevance
“…guineensis, and U. vanhouttei) out of 171 tree species available in the research site (Table 2). The finding that chimpanzees selectively choose tree species to build sleeping platforms is consistent with results from many other research sites (Brownlow et al, 2001;Dutton et al, 2017;Fotang et al, 2021;Furuichi & Hashimoto, 2004;Granier et al, 2014;Hakizimana et al, 2015;Hernandez-Aguilar et al, 2013;Ndiaye et al, 2018;Samson & Hunt, 2014;Stanford & O'Malley, 2008). We showed that the variation in the average tree heights, the abundance of all trees, the abundance of preferred nesting tree species, overall, and per vegetation type may influence sleeping site selection by chimpanzees.…”
Section: Effects Of Horizontal Vegetation Structure On Chimpanzee Sle...supporting
confidence: 90%
See 2 more Smart Citations
“…guineensis, and U. vanhouttei) out of 171 tree species available in the research site (Table 2). The finding that chimpanzees selectively choose tree species to build sleeping platforms is consistent with results from many other research sites (Brownlow et al, 2001;Dutton et al, 2017;Fotang et al, 2021;Furuichi & Hashimoto, 2004;Granier et al, 2014;Hakizimana et al, 2015;Hernandez-Aguilar et al, 2013;Ndiaye et al, 2018;Samson & Hunt, 2014;Stanford & O'Malley, 2008). We showed that the variation in the average tree heights, the abundance of all trees, the abundance of preferred nesting tree species, overall, and per vegetation type may influence sleeping site selection by chimpanzees.…”
Section: Effects Of Horizontal Vegetation Structure On Chimpanzee Sle...supporting
confidence: 90%
“…Evidence supports the hypothesis that chimpanzees may select sleeping sites in the proximity of feeding trees (Basabose & Yamagiwa, 2002; Furuichi & Hashimoto, 2004; Furuichi et al, 2001; Morgan et al, 2018) or where the abundance of their preferred sleeping trees is high (Furuichi & Hashimoto, 2004). On the other hand, the selection of sleeping sites is often determined by factors such as distance to secondary forests, water availability, human activities, elevation, slope, and canopy closure (Fotang et al, 2021; Hernandez‐Aguilar et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and with a mean annual rainfall of 2.4 m p.a, the wet season extending from mid-March to mid-October. Kom Wum is home to seven diurnal and six nocturnal primate species (Fotang et al . 2021).…”
Section: Taxonomic Resultsmentioning
confidence: 99%
“…and with a mean annual rainfall of 2.4 m p.a, the wet season extending from mid-March to mid-October. Kom Wum is home to seven diurnal and six nocturnal primate species (Fotang et al 2021). The plant species of Kom Wum are imperfectly known and there is no checklist of species yet available.…”
Section: Impatiens Etugeimentioning
confidence: 99%